Therapy for hypertension and dyslipidemia: potential of Lipertans (on the example of a clinical observation) - V. V. Kashtalap (Российский кардиологический журнал, 2022)
The article presents epidemiological data on the high prevalence of hypertension and dyslipidemia comorbidity in the general population, as well as shows the leading role of these key cardiovascular risk factors in the development of cardiovascular events. At the same time, within the primary prevention, the adherence of patients to the lipid-lowering therapy remains low. Fixed-dose combinations (Lipertans) based on antihypertensive (amlodipine, perindopril) and lipid-lowering drugs (atorvastatin) can significantly increase the effectiveness of therapy.